Biosensor Applications of MAPLE Deposited Lipase - Califano, Valeria (Biosensors (Basel), 2014)
Matrix Assisted Pulsed Laser Evaporation (MAPLE) is a thin film deposition technique derived from Pulsed Laser Deposition (PLD) for deposition of delicate (polymers, complex biological molecules, etc.) materials in undamaged form. The main difference of MAPLE technique with respect to PLD is the target: it is a frozen solution or suspension of the (guest) molecules to be deposited in a volatile substance (matrix). Since laser beam energy is mainly absorbed by the matrix, damages to the delicate guest molecules are avoided, or at least reduced. Lipase, an enzyme catalyzing reactions borne by triglycerides, has been used in biosensors for detection of β-hydroxyacid esters and triglycerides in blood serum. Enzymes immobilization on a substrate is therefore required. In this paper we show that it is possible, using MAPLE technique, to deposit lipase on a substrate, as shown by AFM observation, preserving its conformational structure, as shown by FTIR analysis.